PERANAN PENGGUNAAN LAHAN DI AREA TANGKAPAN SUNGAI TATAARAN TERHADAP EUTROFIKASI DANAU TONDANO - Claudio Bonifasius; Johan Rombang Johan Rombang; Josephus Kalangi Josephus Kalangi (COCOS, 2020)
ABSTRACTEutrophication is a problem faced by the world today. eutrophication is causedby increasing nutrient concentrations that occur in freshwater ecosystems. Land usechange in this case greatly affects the freshwater ecosystem around the lake. Thisstudy aims to assess the levels of Nitrogen (N) and Phosphorus (P) in the Tataaranriver water flowing into Lake Tondano due land use in the Tataaran river catchmentarea. The method used in this research is survey method and determination ofsampling points based on purposive sampling or the determination according to theresearch objectives, in this case at the outlet of each land use which is then presenteddescriptively for comparison. The results of this study indicate that based on the studyof Nitrogen (N) and Phosphorus (P) levels in the Tataaran river water flowing into LakeTondano, the largest contribution transported comes from residential land use, namelythe average N value content is 56.86 mg / seconds and P of 217.64 mg / second.Keywords : Eutrophication, Landuse, River of Tataaran